Using an Interactive Learning Strategy on Students’ Writing Ability of Procedure Text - Nurdiana, Nurdiana; Roswati, Roswati; afrizal, afrizal; Nazri, Nazri; Susanti, Raden Hariyani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study investigates students' writing ability, both before and after, and the significant difference after using the Interactive Learning Strategy. This study is categorized as pre-experimental, involving one class as a treatment class. For this study, the sample was collected through a purposive sampling technique, which consisted of sixteen students. Eighth-grade students at SMP Negeri 4 Pulau Merbau were involved in this study. Data were analyzed using SPSS version 23. Researchers applied the Wilcoxon signed-rank test to evaluate data. Results showed an extensive difference in the writing skill of students before and after applying the Interactive Learning Strategy, with pre-test gain of 6.25% and post-test gain of 68.0%. Based on the Wilcoxon signed-rank test, it indicates that Ha is acceptable since sig (2-tailed) = 0.000. The decision-making ground for Ha is significant (sig < 0.05), while H0 is significant (sig > 0.05).